2014
DOI: 10.1371/journal.pone.0080664
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Telomeric G-Quadruplexes Dramatically Inhibit DNA Synthesis by Replicative and Translesion Polymerases, Revealing their Potential to Lead to Genetic Change

Abstract: Recent research indicates that hundreds of thousands of G-rich sequences within the human genome have the potential to form secondary structures known as G-quadruplexes. Telomeric regions, consisting of long arrays of TTAGGG/AATCCC repeats, are among the most likely areas in which these structures might form. Since G-quadruplexes assemble from certain G-rich single-stranded sequences, they might arise when duplex DNA is unwound such as during replication. Coincidentally, these bulky structures when present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…4b ). Notably, single-stranded DNA containing four telomeric (GGGTTA) repeats forms intramolecular G-quadruplexes in NaCl solutions 47 49 , suggesting that intramolecular G-quadruplex formation within this particular substrate might be responsible for its reduced unwinding. Therefore, unwinding of *3-way 5′G3.5X and *3-way 5′G4X substrates with 3.5 and 4 repeats, respectively, was analysed in LiCl, which disfavours G-quadruplex formation 45 50 , versus NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…4b ). Notably, single-stranded DNA containing four telomeric (GGGTTA) repeats forms intramolecular G-quadruplexes in NaCl solutions 47 49 , suggesting that intramolecular G-quadruplex formation within this particular substrate might be responsible for its reduced unwinding. Therefore, unwinding of *3-way 5′G3.5X and *3-way 5′G4X substrates with 3.5 and 4 repeats, respectively, was analysed in LiCl, which disfavours G-quadruplex formation 45 50 , versus NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…G-quadruplexes were shown to hinder DNA synthesis by human DNA polymerase δ and several translesion polymerases [169]. Consistently, early studies demonstrated that, in E. coli , repeat loss occurs preferentially during lagging-strand synthesis [170].…”
Section: Replication Barriers Associated With Repeat Dna and Protementioning
confidence: 99%
“…This would be consistent with the observation that WRN-deficient cells show telomere loss during replication. The lost telomere is often in the chromatid derived from lagging strand synthesis, which is more prone to collapse due to G quadruplex formation [102,103,105]. Further work is needed to elucidate whether the role of WRN in proper telomere replication is mediated either by its potential ability to resolve G quadruplexes in the G-rich strand or by its speculated role in telomeric BIR [102,103].…”
Section: Werner's Syndrome Recq Helicase (Wrn)mentioning
confidence: 99%